Minimum wage for Italy: From social justice to productive efficiency - Giovanni Dosi; Maria Enrica Virgillito (Intereconomics, 2024)
This article discusses the case of the minimimum wage for Italy as a policy instrument to foster both social justice and productive efficiency. After briefly reviewing the empirical evidence on the effects of minimum wages upon employment, wage distribution and firm-level reallocation, it presents a series of channels, from the micro to the macro level that can represent transmission mechanisms able to trigger positive feedback loops in the macroeconomic system.
Keywords: J3; D63; O4; 330